PELAKSANAAN DAN FUNGSI PEMELIHARAAN ARSIP PADA DINAS KEARSIPAN DAN PERPUSTAKAAN DAERAH KABUPATEN MAMASA - Rustan IR. (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2018)
This study aims to determine the implementation and maintenance functions of archives in the Regional Archives and Library Office of Mamasa Regency, as well as the factors that influence them. This study the author uses a descriptive qualitative approach that describes the reality of the events under study. The data used in this study are primary data and secondary data. The results showed that the implementation of records management policies in the Office of Archives and Library of Mamasa Regency had not been fully implemented. The factors that support the implementation of records management policies are strong commitment from the Regional Government, availability of equipment, Archival Guidelines, archival training, and provision of incentive officers. While the inhibiting factor is the procedure is too complicated, the lack of awareness and understanding of employees about the importance of the archive, the number of archival officers is still lacking, and the archive is still seen as a less attractive field. The archive management strategy that can be applied is the procurement of archives in the processing unit, the addition of archival officers in the archival unit, changes in the incoming mail control lines, the creation of archival storage schedules and the development of archive functional organizations.